Digital Transformation of E-court on Advocate Practices (Open Society Conference, 2025)
The high number of legal cases in Indonesia has made it difficult for courts to conduct trials. Efforts to increase the number of judges and courtrooms each year have not been sufficient to cope with the surge in cases. As a solution, the Supreme Court has implemented the digitisation of legal services through electronic courts (e-courts), which aim to facilitate parties to proceedings, including advocates, in online trials. This study analyses the impact of the implementation of e-court on the principles of justice and its influence on legal practice. Using a normative approach, the research method focuses on the study of positive legal norms in force to produce arguments, theories, or prescriptions as solutions to legal problems faced. The results of the study indicate that digitalisation through e-court does not alter the essence of judicial values but rather facilitates the conduct of court proceedings and assists lawyers in fulfilling their professional responsibilities. E-court facilitates lawyers in preparing and managing cases more efficiently, as well as providing better representation for their clients. Additionally, e-court offers convenience to the public by saving time and costs when registering and undergoing court proceedings.